Foundations and applications of quantum thermodynamics: coupled double quantum dots heat engines - Oliveira, Jefferson Luan Diniz de (2021)
Quantum thermodynamics is an emergent theory in physics that investigates thermodynamic properties of small systems where the quantum effects become relevant. This study relies upon the proposal of a conceptual design for a quantum thermal machine using a model of coupled double quantum dots (DQDs), each DQD with an excess electron to interact, as the working medium. A general review on the foundations of classical and quantum thermodynamics is provided as well as the characterization of the quantum dots used in the proposed heat engine. The machine operates as an Otto engine in equilibrium conditions; our analysis shows the appearance of different regimes of operations as we adjust external parameters. These operation modes being the heater, the heat engine, or the refrigerator can also be alternated when considering the effects due to the quantum tunneling of a single electron between each quantum dot in the DQDs.